PERUBAHAN MODEL DAN KARAKTERISTIK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MASA PANDEMI COVID-19 - Arista Aulia Firdaus (STKIP PGRI SITUBONDO, 2021)
Abstract The COVID-19 pandemic has changed the model and characteristics of Islamic education learning that has been going on so far. The future of Islamic education is undergoing changes so it is feared that it will experience a setback in education. Work From Home (WFH) policies, social and physical distancing, the process of Teaching and Learning Activities (KBM) using an online system also enlivened the dynamics of Islamic education. This is in accordance with the issuance of an SKB (joint decree) of four ministers regarding the implementation of learning at the beginning of the 2020/2021 school year, and the Decree of the Director General of Education Number 2791 of 2020 concerning emergency curriculum guidelines for madrasas to support learning amid the Covid-19 pandemic. therefore. The ministerial decree above indicates that it is time for reorientation and the role of Islamic education to start accelerating its learning format. This kind of adaptation is a must in responding to the challenges of Islamic education in the COVID-19 pandemic.